Access networks for mobility: a techno-economic model for broadband access technologies - Pereira, João Paulo (2010)
The two main challenges for the access networks are the increasing bandwidth demand and mobility trends. The "triple play" services required (Internet, telephone and TV services) lead to a great increase in bandwidth demand. However, the existing access networks are not able to support this increase, and the capacity to delivery broadband services remain as a challenge ("last mile problem"). The access network remains a bottleneck in terms of the bandwidth and service quality it affords the end user. Besides the bandwidth, other great challenge to access networks is the mobility and the user need to have internet access anywhere and anytime. Then, the increasing demand of "quad-play" (also known as quadruple-play) services, including video, voice, data and mobility, have created new challenges to the modern broadband wireless/wired access networks. This document proposes a techno-economic model to support the new requirements of fixed and nomadic users.